The Effect of the Intraoperative Blood Loss and Intraoperative Blood Transfusion on the Short-Term Outcomes and Prognosis of Colorectal Cancer: A Propensity Score Matching Analysis - Kang, Bing; Liu, Xiao-Yu; Li, Zi-Wei; Yuan, Chao; Zhang, Bin; Wei, Zheng-Qiang; Peng, Dong (Frontiers in Surgery, 2022)
Purpose The purpose of the current study was to analyze the effect of intraoperative blood loss (IBL) and intraoperative blood transfusion (IBT) on the short-term outcomes and prognosis for patients who underwent primary colorectal cancer (CRC) surgery. Methods We retrospectively collected the patients’ information from database of a teaching hospital from Jan 2011 to Jan 2020. IBL and IBT were collected and analyzed and propensity score matching (PSM) analysis was performed. Results A total of 4250 CRC patients were included in this study. There were 1911 patients in the larger IBL group and 2339 patients in the smaller IBL group. As for IBT, there were 82 patients in the IBT group and 4168 patients in the Non-IBT group. After 1:1 ratio PSM, there were 82 patients in the IBT group and 82 patients in the Non-IBT group. The larger IBL group had longer operation time (p=0.000<0.01), longer post-operative hospital stay (p=0.000<0.01), smaller retrieved lymph nodes (p=0.000<0.01) and higher overall complication (p=0.000<0.01) than the smaller IBL group. The IBT group had longer operation time (p=0.000<0.01), longer hospital stay (p=0.016<0.05) and higher overall complications (p=0.013<0.05) compared with the Non-IBT group in terms of short-term outcomes. Larger IBL (p=0.000, HR=1.352, 95% CI=1.142-1.601) and IBT (p=0.044, HR=1.487, 95% CI=1.011-2.188) were independent predictive factors of overall survival (OS). Larger IBL (p=0.000, HR=1.338, 95% CI=1.150-1.558) was an independent predictor of disease-free survival (DFS), however, IBT (p=0.179, HR=1.300, 95% CI=0.886-1.908) was not an independent predictor of DFS. Conclusion Based on the short-term outcomes and prognosis of IBL and IBT. Surgeons should be cautious during the operation and more careful and proficient surgical skills are required for surgeons.